Pengaruh pemasaran internal terhadap komitmen dan kinerja organisasi pada rumah sakit khusus ibu dan anak - Keesa Nabila Afida; Yulia Hendri Yeni; Aguswan Nurdin (Jurnal Kajian Manajemen Bisnis, 2022)
The purpose of this study was to determine the effect of internal marketing on organizational commitment and performance at a special hospital for mothers and children in the city of Padang. The sample criteria in this study were maternal and child hospital employees in the city of Padang who had at least one year of work experience in their current workplace with a sample of 150 respondents. This study uses a questionnaire to collect data and processed using SmartPLS version 3.0 and Microsoft Excel and SPSS 16.0 for descriptive analysis. The results of this study indicate that internal marketing can have a positive influence on organizational commitment and perceived organizational performance of employees. Organizational commitment has a positive influence on organizational performance. Internal marketing has a positive influence on employee perceived organizational performance when mediated (partial mediation 25%) by organizational commitment.